2022
DOI: 10.1371/journal.pone.0274865
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of continuous ketamine infusion for analgosedation in medical and cardiac ICU patients who received mechanical ventilation support: A retrospective cohort study

Abstract: Purpose To assess the effect of continuous ketamine administration in patients admitted to medical and cardiac intensive care units (ICUs) and received mechanical ventilation support. Methods We conducted a retrospective cohort study between March 2012 and June 2020 at an academy-affiliated tertiary hospital. Adult patients who received mechanical ventilation support for over 24 h and continuous ketamine infusion for at least 8 h were included. The primary outcome was immediate hemodynamic safety after conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that ketamine can mimic the response to vasopressor effects in the form of an increase in blood pressure during the initial use of continuous infusion. 6 Therefore, ketamine used for patients in the intensive care unit provides a combination of sedation and analgesia as well as a beneficial effect on hemodynamics. Another study reported lower vasopressor requirements in ventilated patients on continuous ketamine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ketamine can mimic the response to vasopressor effects in the form of an increase in blood pressure during the initial use of continuous infusion. 6 Therefore, ketamine used for patients in the intensive care unit provides a combination of sedation and analgesia as well as a beneficial effect on hemodynamics. Another study reported lower vasopressor requirements in ventilated patients on continuous ketamine.…”
Section: Introductionmentioning
confidence: 99%